2010
DOI: 10.1002/jclp.20722
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of objective personality inventories with sex offenders

Abstract: This review provides a critical analysis of the ability of multiscale inventories to distinguish between sex offender and nonoffender control groups, as well as to discriminate sex offenders from other types of offenders. In addition to expanding upon previous reviews that examined the utility of the Minnesota Multiphasic Personality Inventory (MMPI) with this population (e.g., Levin & Stava, 1987), the current review included studies that utilized other multiscale inventories commonly used in forensic practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
0
18
0
2
Order By: Relevance
“…Other research in correctional settings has examined whether personality inventories, such as the Minnesota Multiphasic Personality Inventory-2 (MMPI-2; Butcher, 2001) or Personality Assessment Inventory (Morey, 1991) can distinguish between known sex offenders and non-sex offenders (Davis and Archer, 2010). Personality inventories are standardized, self-report tests that have traditionally been used in clinical settings to assess mental illness and sets of personality characteristics, but they have also been used by criminal-justice professionals to assess and treat known sex-offender populations (Grover, 2011).…”
Section: Predicting Sexual Assault Perpetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research in correctional settings has examined whether personality inventories, such as the Minnesota Multiphasic Personality Inventory-2 (MMPI-2; Butcher, 2001) or Personality Assessment Inventory (Morey, 1991) can distinguish between known sex offenders and non-sex offenders (Davis and Archer, 2010). Personality inventories are standardized, self-report tests that have traditionally been used in clinical settings to assess mental illness and sets of personality characteristics, but they have also been used by criminal-justice professionals to assess and treat known sex-offender populations (Grover, 2011).…”
Section: Predicting Sexual Assault Perpetrationmentioning
confidence: 99%
“…Personality inventories are standardized, self-report tests that have traditionally been used in clinical settings to assess mental illness and sets of personality characteristics, but they have also been used by criminal-justice professionals to assess and treat known sex-offender populations (Grover, 2011). A review of existing empirical studies testing for differences in personality inventories between sex offenders and non-offenders found that the MMPI (i.e., an earlier version of the MMPI-2) was the most-commonly tested personality inventory with sex-offender populations (Davis and Archer, 2010). Looking across these studies, only one scale, the Pd scale, of the MMPI was consistently found to be elevated in known sex offenders compared with non-sex offenders.…”
Section: Predicting Sexual Assault Perpetrationmentioning
confidence: 99%
“…Nor was there an interaction between childhood abuse and sex offence type committed for any personality dimension of the NEO-FFI. These findings suggest personality differences between groups of sex offenders are more related to abuse they experienced as a child, rather than the type of victim they sexually offended against as an adult, despite the latter being more commonly used to explain findings (Davis & Archer, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…The study of personality in sex offenders has been approached using the type of offence committed as a categorical differentiating variable along with psychopathological constructs of personality, but this has been unable to consistently distinguish sexual from other types of offender (Davis & Archer, 2010). Though many abused children do not show personality *Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…Existing research shows that uncovering criminal personality profiles is a multi‐dimensional analytical problem (Alison, West, & Goodwill, ; D. Canter, ; Egger, ). There are a range of personality theories that contribute to explaining the offender's personality (Jackson & Bekerian, ; Pinizzotto & Finkel, ) and many instruments for exploring the criminal's personality profile (Archer, Buffington‐Vollum, Stredny, & Handel, ; K. M. Davis & Archer, ; Kline, ; Mullen & Edens, ; Nikolova, Hendry, Douglas, Edens, & Lilienfeld, ; Rabin, Borgos, & Saykin, ; Wood, Nezworski, Lilienfeld, & Garb, ). A variety of statistical techniques are also available for analysing these personality tests (Bennell, Goodwill, & Chinneck, ; Goodwill, Allen, & Kolarevic, ; Goodwill et al ., ; Homant & Kennedy, ; Neuman & Wiegand, ).…”
Section: Introductionmentioning
confidence: 99%